Influence of egg pre-storage heating period and storage length on the digestive tract of newly-hatched broiler chicks - Silva, F. H. A.; Faria, D. E.; Torres, K. A. A. [UNESP]; Faria Filho, D. E.; Coelho, A. A. D.; Savino, V. J. M. (Fundação APINCO de Ciência e Tecnologia Avícolas, 2008)
An experiment was carried out to evaluate the effect of different heating times of settable eggs of Cobb 500® broiler breeders before submitting them to different storage periods on body weight, digestive tract organ weights, and intestinal mucosa morphology of newly-hatched chicks. Settable eggs were distributed in a completely randomized experimental design with a 3 x 3 factorial arrangement: pre-storage heating periods (0, 6, 12 hours at 36.92°C) and storage periods (4, 9, 14 days at 12.06°C). Body weight and relative weights of the yolk sac, heart, liver, proventriculus+gizzard, and intestinal segments were measured in chicks hatching at 480 and 498 hours of incubation. Villi height, width and perimeter, and crypt depth (ìm) were measured in duodenal histological sections. It was concluded that pre-storage heating for six hours of eggs stored for four or nine days increases small intestine weight of newly-hatched chicks, but does not influence the morphology of the duodenal mucosa. Pre-storage heating for 12 hours negatively influences body weight and duodenal mucosa development, and therefore this practice is not recommended. Storage length does not have consistent effect on body weight and development of the gastrointestinal tract.
Keywords: Broilers; embryo development; Incubation; intestinal mucosa; morphometrics